The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1071/ar04223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for resistance to two species of root-lesion nematode (Pratylenchus thornei and P. neglectus) in wheat

Abstract: Abstract. Pratylenchus thornei and P. neglectus are two species of root-lesion nematode that cause substantial yield losses in wheat. No commercially available wheat variety has resistance to both species. A doubled-haploid population developed from a cross between the synthetic hexaploid wheat line CPI133872 and the bread wheat Janz was used to locate and tag quantitative trait loci (QTLs) associated with resistance to both P. thornei and P. neglectus. Wheat plants were inoculated with both species of nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 31 publications
2
28
0
2
Order By: Relevance
“…Comparison of maps using common markers revealed that SSR marker locus Xbarc183 on chromosome 6DS was associated with resistance to P. thornei in this study as well as in a second mapping study in which resistance was contributed by a different synthetic hexaploid parent, CPI133872 (Zwart et al 2005). The 6DS QTL contributed by CPI133872 explained 24% of the variation in resistance, which is similar to the value reported here.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Comparison of maps using common markers revealed that SSR marker locus Xbarc183 on chromosome 6DS was associated with resistance to P. thornei in this study as well as in a second mapping study in which resistance was contributed by a different synthetic hexaploid parent, CPI133872 (Zwart et al 2005). The 6DS QTL contributed by CPI133872 explained 24% of the variation in resistance, which is similar to the value reported here.…”
Section: Discussionsupporting
confidence: 77%
“…The 6DS QTL contributed by CPI133872 explained 24% of the variation in resistance, which is similar to the value reported here. QTLs on chromosome 2B for resistance to P. thornei have been detected in other mapping populations (Schmidt et al 2005;Zwart et al 2005). However, due to a lack of common markers on the 2BS region, comparisons between the location of the QTL identified in this study and other P. thornei resistance QTL studies could not be made.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been many studies to identify new sources of resistance to RLN on Middle Eastern wheat varieties and landraces (Nicol et al, 2005;Schimdt et al, 2005;Zwart et al, 2005;Thompson, 2008;Thompson & Seymour 2011;Toktay et al, 2012a). One of the particular relevance to Australian wheat improvement programs were the P. thornei resistant accessions identified among Iranian landraces (Sheedy & Thompson, 2009) and wild relatives of wheat including T. dicoccoides (Sheedy et al, 2012).…”
mentioning
confidence: 99%